2019
DOI: 10.1075/ll.18015.seb
|View full text |Cite
|
Sign up to set email alerts
|

Signs of resistance in the Asturian linguistic landscape

Abstract: A linguistic landscape analysis, grounded in the ideas of contestation and resistance (Blackwood, Lanza, & Woldemariam, 2016; Rubdy & Ben Said, 2015) and carried out using Scollon and Scollon’s (2003) concept of place semiotics, was conducted in four cities located in the Asturias region of Northern Spain. The primary goals of the study were to investigate and interpret the (in)visibility of Asturian, an endangered language spoken primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Jimaima and Banda (2020) combined the insights of Stroud and Mpendukana (2009) with those of Aronin and O'Laoire (2012) in their investigation of materiality in the linguistic landscape in Livingstone Town (Zambia). Similarly, Sebastián (2019) focused on the actual materiality of the signs in his analysis of the linguistic landscape of Asturias in Spain, and he mentions font, material and layering as characteristics, and if the signs were sturdy, durable or fixed.…”
Section: Box 62 Multimodality and Materialitymentioning
confidence: 99%
“…Jimaima and Banda (2020) combined the insights of Stroud and Mpendukana (2009) with those of Aronin and O'Laoire (2012) in their investigation of materiality in the linguistic landscape in Livingstone Town (Zambia). Similarly, Sebastián (2019) focused on the actual materiality of the signs in his analysis of the linguistic landscape of Asturias in Spain, and he mentions font, material and layering as characteristics, and if the signs were sturdy, durable or fixed.…”
Section: Box 62 Multimodality and Materialitymentioning
confidence: 99%
“…Three other minority languages, despite being regionally protected by law, still do not enjoy official status: Aragonese (Aragón 2013), Asturian (Principado de Asturias 1998) and Leonese (Spain 2013). 2 Scholarly research has confirmed the scarcity of Asturian in signage and the militant struggle for its introduction (Sebastian 2019) or the vindicatory presence of Aragonese in the LL (Félez 2017). In addition to these, a growing body of research addresses the role of immigrant languages as new constituents of the Spanish LL.…”
Section: Languages In the Spanish Llmentioning
confidence: 99%
“…and places pierced by histories of violence (Waksman & Shohamy, 2016;Lou & Jaworski, 2016;Seals, 2017;Martín Rojo, 2014a, 2014b. The potential of semiotic resources to disrupt the power of state authorities (Raish, 2019), to problematise the production of inequalities, invisibilities, and exclusion, and to promote social justice has been interrogated in a number of recent studies (Taylor-Leech, 2020;Sebastian, 2019;Moriarty, 2019). Transient linguistic landscapes (henceforth LL) accommodating inscribed violence (Bilkic, 2018), but also harbouring and shaping collective identities of violent protests (Kitis & Milani, 2015), have been discussed as arenas of contestation, exclusion, and dissent (Rubdy & Ben Said, 2015).…”
Section: Manoeuvres Of Dissent In Landscapes Of Annexationmentioning
confidence: 99%